IMPORTANCE OF CRIMINAL PROCEDURE PRINCIPLES IN CRIMINAL PROCEDURE - Djuraev Ikhtiyor Bakhtiyorovich (Scholar Express Journals, 2023)
Some key features of criminal procedures principles are scientifically analyzed and relevant proposals have been put forward in this article. These include the principles of the criminal procedure, its concept, types, legal nature and essence, the principles of the criminal procedure in the course of conducting criminal cases at different stages of the criminal process - pre-trial and judicial stages, and the application of the principles of the criminal procedure and its specific features
Keywords: principle; human right; criminal justice